Gerakan Ekonomi Satyagraha Hindu Bali Melalui Labelisasi Non-Halal Sukla - Jumari Jumari (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: In Bali, the enforcement of Halal Product Guarantee which is a product of law and applicable throughout the territory of NKRI, has gained